A smoker's choice? Identifying the most autonomy-supportive message frame in an online computer-tailored smoking cessation intervention. Issue 5 (4th May 2021) - Altendorf, Maria B.; Smit, Eline S.; Azrout, Rachid; Hoving, Ciska; Weert, Julia C.M van
Abstract: Objective: To test the effect of autonomy-supportive message framing on people's perceived autonomy-support while considering the individual need for autonomy as a moderator. Also, to test whether autonomy-supportive message frames – through increased perceived autonomy-support - lead to more self-determined motivation, and increased intention to quit smoking. Design: An online 2(autonomy-supportive; controlling language) × 2(choice; no choice) between-subjects design with control condition (generic advice) with adult smokers intending to quit ( N = 626). Main outcome: Intention to quit smoking (Theory of Planned Behaviour). Measures: Perceived autonomy-support (Virtual Climate Care Questionnaire), need for autonomy (Health Causality Orientations Scale), self-determined motivation (Treatment Self-Regulation Questionnaire), attitudes, social influence, self-efficacy (I-Change Model). Results: Structural equation modelling revealed no significant effect of autonomy-supportive-message frames on perceived autonomy-support or self-determined motivation, neither did the need for autonomy moderate these effects. Self-determined motivation had a positive, significant effect on intention to quit, mediated by attitudes, social influence, and self-efficacy. Conclusion: Although message frames did not affect perceived autonomy-support or self-determined motivation, higher self-determined motivation increased intention to quit via attitudes, social influence, and self-efficacy. Before drawing the conclusion that message framing has no effect, we recommend to replicate this study in a real-life setting with smokers more likely to read and process the message frames more attentively.